2005
DOI: 10.1152/ajplung.00231.2004
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory response is associated with mortality and severity of infection in sepsis

Abstract: Anti-inflammatory response is associated with mortality and severity of infection in sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 41 publications
1
69
0
3
Order By: Relevance
“…Van den Berg et al [15] assessed the cytokine levels in a murine model with S. aureus bacteremia and showed that levels of IL-1, IL-6, and TNF-α in serum were significantly elevated. Ashare et al [20] also suggested that levels of TNF-α and IL-1β in liver homogenates were increased in septic mice. However, the correlations among these cytokines in S. aureus-induced bacteremia are poorly understood.…”
Section: Il-1β Il-6 and Tnf-αmentioning
confidence: 97%
“…Van den Berg et al [15] assessed the cytokine levels in a murine model with S. aureus bacteremia and showed that levels of IL-1, IL-6, and TNF-α in serum were significantly elevated. Ashare et al [20] also suggested that levels of TNF-α and IL-1β in liver homogenates were increased in septic mice. However, the correlations among these cytokines in S. aureus-induced bacteremia are poorly understood.…”
Section: Il-1β Il-6 and Tnf-αmentioning
confidence: 97%
“…In contrast, overexpression of regulatory cytokines, such as IL-10, may induce overt immunosuppression and thereby increase mortality (67,68). Therefore, an imbalance in the relative production of proinflammatory or antiinflammatory cytokines can lead to serious pathological consequences (69,70).…”
Section: Figurementioning
confidence: 99%
“…technique to detect bacterial translocation in sepsis. PCR is more sensitive than standard plating techniques in that it can quantify exact numbers of bacteria and is able to detect lowlevel bacteremia (31,32). In addition, sepsis is associated with an active cellular and humoral response, resulting in bacterial killing.…”
Section: Discussionmentioning
confidence: 99%